2013
DOI: 10.1038/nnano.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

A surface-patterned chip as a strong source of ultracold atoms for quantum technologies

Abstract: . (2013) A surface-patterned chip as a strong source of ultracold atoms for quantum technologies. Nature Nanotechnology, 8 (5). pp. 321-324. Copyright © 2013 MacMillanA copy can be downloaded for personal non-commercial research or study, without prior permission or chargeThe content must not be changed in any way or reproduced in any format or medium without the formal permission of the copyright holder(s) Laser cooled atoms are central to modern precision measurements 1-6 . They are also increasingly importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 31 publications
3
142
0
Order By: Relevance
“…Prior work has shown that 2D + GMOT flux is maximal for laser intensities near 20 mW/cm 2 , while the 3D GMOT atom number saturates near 50 mW/cm 2 [18]. Both are significantly higher than the 11 mW/cm 2 produced by our laser system.…”
Section: Comparisons and Outlookmentioning
confidence: 55%
See 3 more Smart Citations
“…Prior work has shown that 2D + GMOT flux is maximal for laser intensities near 20 mW/cm 2 , while the 3D GMOT atom number saturates near 50 mW/cm 2 [18]. Both are significantly higher than the 11 mW/cm 2 produced by our laser system.…”
Section: Comparisons and Outlookmentioning
confidence: 55%
“…Custom non-directional etched gratings have been fabricated to this standard for the 3D GMOT [18,25,26], albeit with considerable design time and fabrication cost. Such gratings often require e-beam lithography for small (≈ 500 nm) feature sizes.…”
Section: Theory and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Miniaturized pyramid MOTs, however, suffer from low atom capture rates due to the small volume in which the beams overlap 45,46 , significant backscatter making the atoms difficult to detect 47 , and the geometry making transfer of the atoms to magnetic surface traps non-trivial. A recently demonstrated ver- sion of the tetrahedral-MOT using a planar grating as a reflector (which we refer to as the 'G-MOT', see Figure 2) can capture a large number of atoms, has lower backscatter 48 , and can be easily integrated with atom chip structures 49 . Some disadvantages include the effect of the grating on the wavefronts and polarizations of the manipulation beams 50 , and added difficulty in situations which require several widely-spaced wavelengths.…”
Section: The Magneto Optical Trap Systemmentioning
confidence: 99%